The art of leadership : small things, done well - Lopp, Michael (Ascent Audio, 2021)
Many people think leadership is a higher calling that resides exclusively with a select few who practice and preach big, complex leadership philosophies. But as this practical book reveals, what's most important for leadership is principled consistency. Time and again, small things done well build trust and respect within a team. Using stories from his time at Netscape, Apple, and Slack, Michael Lopp presents a series of small but compelling practices to help you build leadership skills. You'll learn how to create teams that are highly productive, highly respected, and highly trusted. Lopp has been speaking and writing about this topic for over a decade and now maintains a Slack leadership channel with over 13,000 members. The essays in this book examine the practical skills Lopp learned from exceptional leaders-as a manager at Netscape, a senior manager and director at Apple, and an executive at Slack. You'll learn how to apply these lessons to your own experience.